2023
DOI: 10.1002/1878-0261.13477
|View full text |Cite
|
Sign up to set email alerts
|

The LIN28B–let‐7–PBK pathway is essential for group 3 medulloblastoma tumor growth and survival

Shubin W. Shahab,
Christianna M. Roggeveen,
Jiarong Sun
et al.

Abstract: Children with Group 3 medulloblastoma (G3 MB) have a very poor prognosis, and many do not survive beyond 5 years after diagnosis. A factor that may contribute to this is the lack of available targeted therapy. Expression of protein lin‐28 homolog B (LIN28B), a regulator of developmental timing, is upregulated in several cancers, including G3 MB, and is associated with worse survival in this disease. Here, we investigate the role of the LIN28B pathway in G3 MB and demonstrate that the LIN28B–lethal‐7 (let‐7; a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Through consulting the literature, we were particularly interested in PBK, which is overexpressed in several human malignancies. [20][21][22][23][24] By analyzing the amino acid sequence of PBK, we found that PBK at Thr9 may be the potential phosphorylation site of CDK5. To further verify that CDK5 phosphorylates PBK-T9, HEK293 cells were transfected with GFP-CDK5 and FLAG-PBK.…”
Section: Phosphorylation Of Pbk At Thr9 By Cdk5 Promotes Cell Prolife...mentioning
confidence: 99%
“…Through consulting the literature, we were particularly interested in PBK, which is overexpressed in several human malignancies. [20][21][22][23][24] By analyzing the amino acid sequence of PBK, we found that PBK at Thr9 may be the potential phosphorylation site of CDK5. To further verify that CDK5 phosphorylates PBK-T9, HEK293 cells were transfected with GFP-CDK5 and FLAG-PBK.…”
Section: Phosphorylation Of Pbk At Thr9 By Cdk5 Promotes Cell Prolife...mentioning
confidence: 99%
“…Like DNA-binding proteins, small-molecule inhibition of RBPs is difficult, although recent high-throughput approaches have generated candidates ( Wu, 2020 ). The most promising LIN28(A/B) inhibitor is C1632, which targets LIN28B + cell lines both by disruption of LIN28B–let-7 interaction ( Franses et al, 2020 ; Zhang Q. et al, 2023 ; Shahab et al, 2023 ) and in Ewing sarcoma by disruption of the interaction between EWS-FLI1 mRNA and LIN28B ( Keskin et al, 2020 ). Other molecules such as LI71 bind the cold shock domain and have efficacy against LIN28B + cancer cell lines ( Wang L. et al, 2018 ).…”
Section: Targeting Aberrant Stem Cell Programs In Leukemia For Therapymentioning
confidence: 99%